Removal of Hexavalent Chromium from Wastewater using Modified Multiwall Carbon Nanotubes - Dokmaji, Tamara Georgesaleh (2018)
A Master of Science thesis in Chemical Engineering by Tamara Georgesaleh Dokmaji entitled, “Removal of Hexavalent Chromium from Wastewater using Modified Multiwall Carbon Nanotubes”, submitted in December 2018. Thesis advisor is Dr. Taleb Ibrahim and thesis co-advisor is Dr. Mustafa Khamis. Soft and hard copy available.